DIGITALIZASION OF ENGLISH LEARNING MEDIA AT UNIVERSITY OF MAHKOTA TRICOM UNGGUL (CASE STUDY) - Roni Juliansyah; Rosihan Arbi Said; Masniati Murni Ritonga (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
Various changes in English curriculum starting from the audio-lingual method to the communicative competence used today have not been able to improve students' English skills. The teacher-centered pattern that has changed to student-centered has also not been able to provide significant changes to student learning outcomes at the university level. This study was conducted to investigate the digitalizaton of English Learning at University of Mahkota Tricom Unggul which was troubled in shiffting the learning landscape from offline to online or digital based. It would be done by applying qualitative research. The data was taken from interview of English lecturers and EFL students majoring from D-3 Akuntansi and S-1 Managemen. The interview questions were settled as well based on the digitalization in English Learning and the Problem they met. After analysing the data, it was found that the students commonly used e-learning, Zoom and Whatsapp. E-learning was used by them for creating and sharing the material of the study, Zoom was used for undergoing a class meeting and whatsapp was used to accomodate interaction behind the teaching learning time. The most common problem that they faced in running this digitalization was that the limitation of the digital media device, less internet connection up to less learning system management.